2016
DOI: 10.18632/oncotarget.8639
|View full text |Cite
|
Sign up to set email alerts
|

High risk of deep vein thrombosis associated with peripherally inserted central catheters in lymphoma

Abstract: Peripherally inserted central venous catheters (PICCs) are widely used in cancer patients. Although PICC is a convenient tool, its use is associated with an obvious increase in the incidence of venous thrombosis. The risk factors for deep vein thrombosis associated with the use of PICCs in cancer patients are largely unexplored. This study aimed to investigate the incidence of PICC-associated thrombosis in lymphoma compared with its incidences in other types of cancer. A total of 8028 adult cancer patients ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
(31 reference statements)
0
21
0
5
Order By: Relevance
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] ( Table 1). Four additional studies were identified by cross-referencing in the 21 published reports.…”
Section: Methodsologymentioning
confidence: 99%
See 3 more Smart Citations
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] ( Table 1). Four additional studies were identified by cross-referencing in the 21 published reports.…”
Section: Methodsologymentioning
confidence: 99%
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] (Table 1). Patients included into these studies were identified by institutional databases in 14 studies [7,8,[10][11][12][13][14][15][16][18][19][20][21]30], by the local hospital discharge registry in one study [17], by cancer registries in four studies (California Cancer Registry [27], VA Cancer registry [25], Swedish cancer registry [29], Danish lymphoma database [28]), by clinical trial registries in five ...…”
Section: Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it also induces complications, and catheter-related venous thrombosis is one of its serious complications. 1 , 2 Once thrombosis occurs, transfusion through the PICC catheter is stopped, anticoagulant and thrombolytic therapy are given, and chemotherapy time is delayed. It affects the long-term curative effect of breast cancer treatment and even endangers the patient’s life when it becomes severe.…”
Section: Introductionmentioning
confidence: 99%